Newswork in crisis: Sourcing patterns during COVID-19 through a 'lived experience' perspective - Spyridou, Lia Paschalia; Vatikiotis, Pantelis; Maniou, Theodora A. (My University, 2023)
During crises the newsmedia are expected to provide relevant and accurate information to help citizens comprehend the crisis and act upon it. As a source-driven practice, journalism relies on a variety of sources to validate news and provide perspectives. The disruptive nature of a crisis though raises questions about how journalists select sources and what these choices say about professional autonomy and criticality. Considering source choices as newsgathering venues and strategies, and drawing on semi-structured interviews with journalists in Greece and Cyprus, the study explores the factors that shaped journalists’ sourcing practices during the COVID-19 crisis. We find that journalists over-relied on political sources and selective authoritative voices compromising the tenets of verification and independence. The fear to convey inaccurate or ‘biased’ information amid disinformation flows, bolstered journalist's elite orientation. Professional precarity and economic pressures are found to further worsen the ‘lived experience’ of journalists limiting their ability to question and scrutinise power in times of crises.
Keywords: Sources; Sourcing practices; Risk journalism; Social media; Elite sources; Autonomy; Precarity; Cyprus; Greece